Role of nitrogen fertilization in sustaining organic matter in cultivated soils - Ladha, Jagdish K.; Reddy, C. Kesava; Padre, Agnes T.; van Kessel, Chris (Wiley, 2011)
Soil organic matter (SOM) is essential for sustaining food production and maintaining ecosystem services and is a vital resource base for storing C and N. The impact of long‐term use of synthetic fertilizer N on SOM, however, has been questioned recently. Here we tested the hypothesis that long‐term application of N results in a decrease in SOM. We used data from 135 studies of 114 long‐term experiments located at 100 sites throughout the world over time scales of decades under a range of land‐management and climate regimes to quantify changes in soil organic carbon (SOC) and soil organic nitrogen (SON). Published data of a total of 917 and 580 observations for SOC and SON, respectively, from control (unfertilized or zero N) and N‐fertilized treatments (synthetic, organic, and combination) were analyzed using the SAS mixed model and by meta‐analysis. Results demonstrate declines of 7 to 16% in SOC and 7 to 11% in SON with no N amendments. In soils receiving synthetic fertilizer N, the rate of SOM loss decreased. The time‐fertilizer response ratio, which is based on changes in the paired comparisons, showed average increases of 8 and 12% for SOC and SON, respectively, following the application of synthetic fertilizer N. Addition of organic matter (i.e., manure) increased SOM, on average, by 37%. When cropping systems fluctuated between flooding and drying, SOM decreased more than in continuous dryland or flooded systems. Flooded rice (Oryza sativa L.) soils show net accumulations of SOC and SON. This work shows a general decline in SOM for all long‐term sites, with and without synthetic fertilizer N. However, our analysis also demonstrates that in addition to its role in improving crop productivity, synthetic fertilizer N significantly reduces the rate at which SOM is declining in agricultural soils, worldwide.